Pengaruh Konflik antara Pekerjaan-Keluarga pada Kinerja Karyawan dengan Kelelahan Emosional sebagai Variabel Pemediasi (Universitas Negeri Semarang, 2015)
The purpose of this study was to find out whether there were the effects of work-family conflict on lecturer’s performance with emotional exhaustion as the mediating variable.The population of this study wasthe lecturers of Semarang State University. The total sample used in this study were92 lecturers of Semarang State University. The method of data collectionby quetionares.The results of the study showed that there was a significant positive influence of work-family conflict on emotional fatigue. The results also showed that there was a significant negative effect of emotional fatigue on the performance of lecturers. While the work-family conflict showed negative results but there were no significant effects on the performance of the lecturers. Emotional fatigue was proved that it mediated between the relationship of work-family conflict and lecturer’s performance.